Heavy metal contamination of Hg and Pb in water, sediment and Violet Batissa (Batissa violacea Lamark, 1818) meat in Teunom River, Aceh Jaya Regency, Indonesia - Fauziah, Fauziah; Abdullah, Abdullah; Supriatno, Supriatno; Firdus, Firdus; Nasir, Muhammad; Mellisa, Siska; Batubara, Agung Setia (Depik, 2021)
Violet Batissa (Batissa violacea) is an important economic organism on the west-south coast of Aceh, because it is relatively high consumed by the community. However, gold mining activities carried out around the watershed are estimated to pollute the river and cause B. violacea to also be affected. The purpose of this study was to determine the level of mercury (Hg) and Lead (Pb) contamination in clam meat in Teunom, Aceh Jaya Regency. The research was conducted from June to September 2021. Sampling of clam was done by purposive sampling method. Hg and Pb were analyzed in clam meat using the Atomic Absorption Spectrophotometer (AAS) method. The results of the analysis showed that the Hg content in clam meat was between 0.12-0.63 mg/kg (mean 0.350.26 mg/kg), water 0.0026-0.0103 mg/kg (mean 0.00520.004 mg/kg), and sediment 1.3224-3.8767 mg/kg (mean 2.23241.427 mg/kg). Furthermore, the results of the analysis showed that the Pb content in clam meat, water and sediment had the same value at 3 stations with values 0.00020 mg/kg, 0.00030 mg/kg, and 0.00020 mg/kg, respectively. The conclusion of this study is that the Hg content in water and sediment has exceeded the threshold, while the clam meat is still in good quality standards. The Pb content in clam meat, water and sediment were also in good quality standards. Based on our study, B. violacea is still safe for consumption, while the water has been polluted and is recommended not to be utilized for human consumption.Keywords:Heavy metalRiverWaterSedimentBatissa violacea